Effects of Survival Processing on Item and Context Memory: Enhanced Memory for Survival-Relevant Details - Meyers, Zoie R.; McCurdy, Matthew P.; Leach, Ryan C.; Thomas, Ayanna K.; Leshikar, Eric D. (Frontiers in Psychology, 2020)
Due to natural selection pressure, certain aspects of memory may have been selected to give humans a survival advantage. Research has demonstrated that processing information for survival relevance leads to better item memory (i.e., the content of information) compared to control conditions. The current study investigates the effects of survival processing on context memory (i.e., memory for peripheral episodic details) and item memory to better understand when the survival processing memory advantage emerges. In this study, participants viewed objects in either a plausible color, for example a red apple, or in an implausible color, such as a green pie. We chose this color plausibility manipulation because color is a detail that conveys information about the fitness of an item. After studying items in either a survival or moving (control) condition, participants made item memory judgments (did you see this item before?), and two context memory judgments: color context (in which color did you see this item?), and source context (in which condition did you see this item?). Results indicated better item memory for materials processed in the survival relative to moving condition. Critically, for color context there was a condition by plausibility interaction, where memory was best for plausibly colored items in the survival processing condition. There was no difference, however, in source context memory between the survival and moving conditions. These results suggest the survival processing memory advantage extends to some contextual details, but only those details that tap into the survival utility of items, such as color.